Maintenance of neural stem cell regional identity in culture. Issue 1 (1st January 2016) - Delgado, Ryan N.; Lu, Changqing; Lim, Daniel A.
ABSTRACT: Neural stem cells (NSCs) are distributed throughout the ventricular-subventricular zone (V-SVZ) in the adult mouse brain. NSCs located in spatially distinct regions of the V-SVZ generate different types of olfactory bulb (OB) neurons, and the regional expression of specific transcription factors correlates with these differences in NSC developmental potential. In a recent article, we show that Nkx2.1 -expressing embryonic precursors give rise to NKX2.1+ NSCs located in the ventral V-SVZ of adult mice. Here we characterize a V-SVZ monolayer culture system that retains regional gene expression and neurogenic potential of NSCs from the dorsal and ventral V-SVZ. In particular, we find that Nkx2.1 -lineage V-SVZ NSCs maintain Nkx2.1 expression through serial passage and can generate new neurons in vitro . Thus, V-SVZ NSCs retain key aspects of their in vivo regional identity in culture, providing new experimental opportunities for understanding how such developmental patterns are established and maintained during development.